2020
DOI: 10.19102/icrm.2021.120205
|View full text |Cite
|
Sign up to set email alerts
|

Acute Safety and Efficacy of Fluoroless Cryoballoon Ablation for Atrial Fibrillation

Abstract: Pulmonary vein isolation (PVI) is widely used for the ablation of atrial fibrillation, with prior reports suggesting good efficacy. Due to the widespread use of three-dimensional electroanatomic mapping systems and advances in intracardiac echocardiography, fluoroless ablation has been made possible. Fluoroless ablation with a cryoballoon (CB), however, has not been widely performed because of the need to prove occlusion of the vein with contrast dye and fluoroscopy. The objective of this study is to show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Alyesh et al . 12 conducted a first-of-its-kind, proof-of-concept case–control study comparing fluoroless CBA with the traditional fluoroscopic technique. The procedure was exclusively performed under ICE guidance and employed ICE imaging combined with haemodynamic measures with continuous-wave pressure monitoring (CWPM).…”
Section: Discussionmentioning
confidence: 99%
“…Alyesh et al . 12 conducted a first-of-its-kind, proof-of-concept case–control study comparing fluoroless CBA with the traditional fluoroscopic technique. The procedure was exclusively performed under ICE guidance and employed ICE imaging combined with haemodynamic measures with continuous-wave pressure monitoring (CWPM).…”
Section: Discussionmentioning
confidence: 99%
“…Alyesh et al, 14 reported on the use of non‐fluoroscopic methods for patients undergoing CB PVI with a fluoroless approach and compared to a control group with traditional fluoroscopic techniques. Temperature at 30 s, minimum temperature, time to isolation, and procedural length and complications were evaluated.…”
Section: Why Reduce Fluoroscopy?mentioning
confidence: 99%
“…This last method may be more difficult to visualize but can provide useful information about the location of a potential leak (Supporting Information: Video 10). Alyesh et al, 14 reported on the use of non-fluoroscopic methods for patients undergoing CB PVI with a fluoroless approach and compared to a control group with traditional fluoroscopic techniques. Temperature at 30 s, minimum temperature, time to isolation, and procedural length and complications were evaluated.…”
Section: Step 4-parameters To Achieve Pulmonary Vein Occlusionmentioning
confidence: 99%
See 2 more Smart Citations